1986
DOI: 10.1111/j.1600-0609.1986.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet peroxidase of circulating thrombocytes in acquired refractory anaemias

Abstract: The platelet peroxidase (PPO) content of circulating thrombocytes was determined in 10 healthy controls and in 18 cases of acquired refractory anaemia (2 with refractory anaemia, 4 with sideroblastic refractory anaemia, 8 with refractory anaemia with excess of blasts, 3 with refractory anaemia in transformation and 1 with chronic myelomonocytic leukaemia). The thrombocytes of the controls were invariably PPO‐positive. No peroxidase deficiency was found in the 4 patients with sideroblastic refractory anaemia. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Third, we found that SKK-1 showed a partial response to the differentiation cue all-trans retinoic acid (ATRA) reflected in a reduction of the proportion of CD117 + cells as assessed by flow cytometry (Figure 2A ). In terms of cytology, we observed a reduction in basophilia after May-Grünwald-Giemsa staining ( Supplementary Figure 3A ), a further characteristic of differentiation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Third, we found that SKK-1 showed a partial response to the differentiation cue all-trans retinoic acid (ATRA) reflected in a reduction of the proportion of CD117 + cells as assessed by flow cytometry (Figure 2A ). In terms of cytology, we observed a reduction in basophilia after May-Grünwald-Giemsa staining ( Supplementary Figure 3A ), a further characteristic of differentiation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%